Perubahan Konstitusi dan Reformasi Ketatanegaraan Indonesiaa - Abu Tamrin (Jurnal Cita Hukum, 2015)
Abstract: Amendment of the Constitution and constitutional reform in Indonesia. The Constitution can be two meanings, namely: a broad sense and narrow sense. Meaning constitution means forming. Constitutional expert in Constitutional Law contains basic law is written. Act of 1945 is a formal document which is the result of political struggle in the past. In the era of the New Order Act of 1945 "sacred" so that the People's Consultative Assembly of Indonesia in the New Order era did not alter the Constitution of 1945. In the reform era to amend the Act of 1945. There was a change of articles of Law 1945. One only Article 1 (2) the first amendment of the Constitution of 1945. Sovereignty is in the people's hands and performed in accordance with the Constitution. There is a state agency that was formed, one of which the Constitutional Court and no state institutions were removed, the Supreme Advisory Council. With the change of the Constitution of 1945, then there was a constitutional reform in Indonesia Abstrak: Perubahan Konstitusi dan Reformasi Ketatanegaraan Indonesia. Menurut K.C. Wheare kata konstitusi dapat menjadi 2 arti yaitu: arti luas dan arti sempit. Menurut Wirjono Projodikoro arti konstitusi berarti membentuk. Baik konstitusi maupun Undang-undang Dasar menurut Pakar Hukum Tata Negara berisi Hukum dasar tertulis. Konstitusi/Undang-undang Dasar 1945 merupakan dokumen formal yang merupakan hasil perjuangan politik bangsa di waktu lampau. Di era orde baru Undang-undang Dasar 1945 “disakralkan” sehingga Majelis Permusyawaratan Rakyat RI di era orde baru tidak mengubah Undangundang Dasar 1945. Di era reformasi dilakukan perubahan Undang-undang Dasar 1945. Ada perubahan pasal Undang-undang Dasar 1945. Salah satunya Pasal 1 ayat (2) perubahan pertama Undang-undang Dasar 1945.Kedaulatan ada di tangan rakyat dan dilakukan menurut Undang-undang Dasar. Ada lembaga negara yang dibentuk, salah satunya Mahkamah Konstitusi RI dan ada lembaga tinggi negara yang dihapus, yaitu Dewan Pertimbangan Agung RI.Dengan adanya perubahan Undang-Undang Dasar 1945, maka terjadi reformasi ketatanegaraan Indonesia. DOI: 10.15408/jch.v2i1.1843